Pengaruh Jumlah Penduduk, Tingkat Pendidikan, Inflasi dan Pengangguran terhadap Tingkat Kemiskinan di Kabupaten Flores Timur Tahun 2013-2022 - Tajriah, Suryati; Sagajoka, Estherlina; Djata, Baltasar Taruma (JURNAL EQUILIBRIUM, 2024)
This study aims to determine the effect of population, education level, inflation and unemployment on poverty levels in East Flores District partially and simultaneously. This study uses quantitative research methods with the analysis technique used is the semilog linear regression model. To calculate the linear regression equation, the semilog model data must meet the classical assumption test and hypothesis test. This is evidenced by the results of the parametric significant test (t test). The coefficient value of the population variable is 2,322 with tcount<ttable (2,325>2,015), the coefficient value of the education level variable is -14.502 with tcount<ttable (-2.307<2,015), the inflation variable coefficient value is -0.784 with tcount<ttable (-4.781<2,015) and the coefficient value of the unemployment variable is 3.736 with tcount>ttable (3.401>2,015). Then for the F test, the value of Fcount>Ftable(7.642>5.19) is obtained. Based on the results of the calculation of the t test, it can be concluded that the population variable has no effect on the poverty level because the addition of the population is followed by a higher increase of other factors which are indicated to reduce poverty such as increased income in the community, causing a high poverty rate. goverment to finance his education thereby reducing the poverty rate in East Flores Regency. Inflation has a negative effect on the level of poverty, even though there is inflation, the poor are still able to meet their needs and unemployment affects the level of poverty because the unemployed are people who do not have jobs and income so they cannot make ends meet. Based on the F test that population, education level, inflation and unemployment simultaneously affect the level of poverty in East Flores Regency.